Building Holistic Islamic Education Towards Society 5.0: A Critical Study of Al-Syaibany's Ideas - Hermawati, Kiki; Fofied, Johanis Valentino (Abdurrauf Journal of Islamic Studies, 2025)
This research analyses Al-Syaibany's thoughts on Islamic education in the context of the Society 5.0 era. The aim is to explore the relevance of Al-Syaibany's curriculum concepts and learning methods to the needs of modern education that focuses on humans and technology. The research method uses a qualitative approach with a literature study, referring to Al-Syaibany's main book, Falsafah Pendidikan Islam, as well as secondary sources such as journals and related books. The results show that Al-Syaibany's curriculum emphasises the balance between religious values, the development of learners' potential, and relevance to the needs of society. The principles include harmony with religion, comprehensiveness, balance of knowledge, and adaptation to social change. In addition, his learning methods, such as problem-based methods and discussions, are in line with the demands of Society 5.0 which requires critical thinking skills, collaboration, and digital literacy. This research concludes that Al-Syaibany's thinking can be a solution to the challenges of education in the Society 5.0 era, especially in integrating Islamic values with technological advances. The implication is that educators and policy makers can adopt this concept to create a holistic and adaptive education system. [Penelitian ini menganalisis pemikiran Al-Syaibany tentang pendidikan Islam dalam konteks era Society 5.0. Tujuannya adalah untuk mengeksplorasi relevansi konsep kurikulum dan metode pembelajaran Al-Syaibany dengan kebutuhan pendidikan modern yang berfokus pada manusia dan teknologi. Metode penelitian menggunakan pendekatan kualitatif dengan studi literatur, mengacu pada buku utama Al-Syaibany, Falsafah Pendidikan Islam, serta sumber sekunder seperti jurnal dan buku terkait. Hasil penelitian menunjukkan bahwa kurikulum Al-Syaibany menekankan keseimbangan antara nilai agama, pengembangan potensi peserta didik, dan relevansi dengan kebutuhan masyarakat. Prinsip-prinsipnya mencakup keselarasan dengan agama, komprehensivitas, keseimbangan ilmu, serta adaptasi terhadap perubahan sosial. Selain itu, metode pembelajarannya, seperti metode berbasis masalah dan diskusi, sejalan dengan tuntutan Society 5.0 yang membutuhkan keterampilan berpikir kritis, kolaborasi, dan literasi digital. Penelitian ini menyimpulkan bahwa pemikiran Al-Syaibany dapat menjadi solusi untuk menghadapi tantangan pendidikan di era Society 5.0, terutama dalam mengintegrasikan nilai Islam dengan kemajuan teknologi. Implikasinya, pendidik dan pemangku kebijakan dapat mengadopsi konsep ini untuk menciptakan sistem pendidikan yang holistik dan adaptif.]